2019
DOI: 10.3390/ijms20236027
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Capability of Roxadustat (FG-4592), an Oral HIF Prolyl-Hydroxylase Inhibitor, to Perturb Membrane Ionic Currents: An Unidentified yet Important Action

Abstract: Roxadustat (FG-4592), an analog of 2-oxoglutarate, is an orally-administered, heterocyclic small molecule known to be an inhibitor of hypoxia inducible factor (HIF) prolyl hydroxylase. However, none of the studies have thus far thoroughly investigated its possible perturbations on membrane ion currents in endocrine or heart cells. In our studies, the whole-cell current recordings of the patch-clamp technique showed that the presence of roxadustat effectively and differentially suppressed the peak and late comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…Indeed, previous studies have demonstrated the presence of I h and I K(DR) in endocrine cells, such as pancreatic αor β-cells [4][5][6]11,39]. The I K(DR) presented herein (i.e., K V 2.1-encoded current) has been reported to be functionally enriched in different types of heart cells [25,26,40,41]. Consequently, it is possible that the mediation by CIL of I K(DR) inhibition influences the heart function to a certain extent, as previously reported with respect to the effectiveness of aconitine, a potent cardiotoxin, in the amplitude and gating of depolarization-triggered I K(DR) in heart cells [41].…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Indeed, previous studies have demonstrated the presence of I h and I K(DR) in endocrine cells, such as pancreatic αor β-cells [4][5][6]11,39]. The I K(DR) presented herein (i.e., K V 2.1-encoded current) has been reported to be functionally enriched in different types of heart cells [25,26,40,41]. Consequently, it is possible that the mediation by CIL of I K(DR) inhibition influences the heart function to a certain extent, as previously reported with respect to the effectiveness of aconitine, a potent cardiotoxin, in the amplitude and gating of depolarization-triggered I K(DR) in heart cells [41].…”
Section: Discussionmentioning
confidence: 51%
“…This type of ionic current has been regarded to be carried by channels of the hyperpolarization-activated cyclic nucleotide-gated (HCN1-4) gene family, which belongs to the superfamily of voltage-gated K + channels and cyclic nucleotide-gated channels [8,12,18,20].Voltage-gated K + (K V ) channels play essential roles in determining membrane excitability, and the delayed rectifier K + channels, such as K V 3 (KCNC) and K V 2 (KCNB) channels, are ubiquitous in endocrine cells [21][22][23][24]. A causal relationship between the K V 3 or K V 2 channel and the delayed rectifier K + current (I K(DR) ) has been previously established [21,23,25,26]. The K V channels from the K V 3.1-K V 3.2 types, the biophysical properties of which exhibit to have positively shifted voltage dependency and fast deactivation rate, are the major determinants of I K(DR) identified in the pituitary tumor (GH 3 ) cells [23,24,26].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The causal link between the delayed-rectifier K + current ( I K(DR) ) and K V 3/K V 2 channels has been previously disclosed ( Yeung et al., 2005 ; Wang et al., 2008 ; Huang et al., 2013 ; Chang et al., 2019 ; Lu et al., 2019 ). The biophysical characteristics of K V 3.1-K V 3.2 channels, which are the dominant factors of I K(DR) identified in pituitary tumor (GH 3 ) cells ( Chang et al., 2019 ; Lu et al., 2019 ; So et al., 2019 ), show a positively shifted voltage dependency as well as fast deactivation rate. However, whether and how RDV effects the adjustments on the amplitude and kinetic gating of above-stated types of K + currents still requires investigations.…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, K V 3 (KCNC) and K V 2 (KCNB), two delayed-rectifier K + channels, are widespread in different excitable cells such as endocrine cells (Lien and Jonas, 2003;Wang et al, 2008;Fletcher et al, 2018;Kuo et al, 2018;Lu et al, 2019;So et al, 2019). The causal link between the delayedrectifier K + current (I K(DR) ) and K V 3/K V 2 channels has been previously disclosed (Yeung et al, 2005;Wang et al, 2008;Huang et al, 2013;Chang et al, 2019;Lu et al, 2019). The biophysical characteristics of K V 3.1-K V 3.2 channels, which are the dominant factors of I K(DR) identified in pituitary tumor (GH 3 ) cells (Chang et al, 2019;Lu et al, 2019;So et al, 2019), show a positively shifted voltage dependency as well as fast deactivation rate.…”
Section: Introductionmentioning
confidence: 99%